Engineering Natural Pollen Grains as Multifunctional 3D Printing Materials (Adv. Funct. Mater. 49/2021). (2nd December 2021) - Chen, Shengyang; Shi, Qian; Jang, Taesik; Ibrahim, Mohammed Shahrudin Bin; Deng, Jingyu; Ferracci, Gaia; Tan, Wen See; Cho, Nam‐Joon; Song, Juha
Abstract : 3D Printing Materials The development of 3D printing materials from natural resources is essential in sustainable additive manufacturing. In article number 2106276, Nam‐Joon Cho, Juha Song, and co‐workers engineer pollen‐derived microgel suspension as reinforcements for hydrogel inks and as supporting matrices for freeform 3D printing systems. Pollen grains are attractive candidates to engineer advanced materials for 3D printing applications owing to their natural abundance, renewability, affordability, processibility, monodispersity, and tunable rheological features.